Paradigm shift in pathophysiology of vasomotor symptoms: Effects of estradiol withdrawal and progesterone therapy. (2020) - Fan, Yubo; Tang, Ruiyi; Prior, Jerilynn C.; Chen, Rong
Highlights: Withdrawal from high brain estrogen (E2) causes neuroendocrine stress hormone spikes. Norepinephrine (NE) causes thermoneutral narrowing of vasomotor symptoms (VMS). VMS and psychosocial stress (anxiety, depression) bidirectionally relate and to NE. Progesterone suppresses central NE and decreases VMS in peri- and menopausal women. Progesterone therapy may allow women to stop E2 for VMS without rebound symptoms. Abstract : Purpose: It was previously thought that estrogen deficiency caused hot flushes and night sweats or vasomotor symptoms (VMS). However, VMS also present in women in the Late Reproductive Transition or "Very Early Perimenopause" who still have regular menstrual cycles and whose estrogen levels have not decreased. Social emotional stresses increase VMS that, in turn, increase stress hormones and mood changes. Evidence suggests that downward swings of estradiol (E2) cause the dramatic neuroendocrine/cytokine release with elevated central norepinephrine levels leading to thermoneutral zone narrowing and VMS. There are aspects of the physiology of VMS that resemble "estrogen addiction ". The aim of this review is to integrate scientific and clinical VMS knowledge in a new paradigm within the model of balanced estradiol and progesterone levels for women's optimal health. Major sources of information: We reviewed studies focusing on VMS and its risk factors, pathophysiology and treatment on PubMed, MEDLINE, and EMBASE. Data synthesis in the context of E2-P4 balance women's health model: Estrogen withdrawal stimulates release of a host of cytokines and neurotransmitters most important of which is increased NE. Downward E2 levels are also associated with anxiety and depression. Initially premenopausal women made menopausal by bilateral ovariectomy/chemotherapy with rapid E2 decline are more likely to report severe VMS than those with natural reproductive aging. When E2 levels drop, increased central NE neuroendocrine-thermal dysregulation triggers hot flushes/night sweats. Although E2-based menopausal hormone therapy relieves VMS, its discontinuation often produces a VMS rebound. P4 relieves VMS in both menopausal and perimenopausal women likely by decreasing or stabilizing NE. We hypothesize that the rebound on discontinuing E2 therapy could be prevented by first adding P4 and then gradually weaning off E2. This paradigm shift's clinical and research relevance: The effects—of E2 withdrawal, and high E2 levels to increase, and of full dose P4 to suppress central NE levels—need further documentation. Several primate studies and clinical and controlled trials are needed to test this new model. Conclusions: High brain E2 exposure followed by E2 withdrawal rather than low estrogen per se is the underlying cause of VMS; P4 counterbalances the varying E2 levels in the premenopausal years. P4 therapy in perimenopause/menopause may effectively decrease or prevent hot flushes/night sweats without the risk of withdrawal VMS increases that are related to stopping E2 therapy.